The Reversal of Memory Deficits in an Alzheimer’s Disease Model Using Physical and Cognitive Exercise - Dare, Leticia R.; Garcia, Alexandre; Soares, Caroline B.; Lopes, Luiza; Neves, Ben-Hur S.; Dias, Daniel V.; Mello-Carpes, Pâmela B. (Frontiers in Behavioral Neuroscience, 2020)
Alzheimer’s disease (AD) is the leading cause of dementia in the world, accounting for 50%–75% of cases. Currently, there is limited treatment for AD. The current pharmacological therapy minimizes symptom progression but does not reverse brain damage. Studies focused on nonpharmacological treatment for AD have been developed with the aim of acting on brain plasticity and minimizing the neurotoxicity caused by the amyloid-beta (Aβ) peptide. Using a neurotoxicity model induced by Aβ in rats, the present study shows that physical and cognitive exercise reverse recognition memory deficits (with a prominent effect of long-term object recognition memory), decrease hippocampal lipid peroxidation, restore the acetylcholinesterase activity altered by Aβ neurotoxicity, and seems to reverse, at least partially, hippocampal tissue disorganization.